Quality of Work-Life During Pandemic Data Analysis and Mathematical Modeling - Shinde, Gitanjali Rahul; Majumder, Soumi; Bhapkar, Haribhau R.; Mahalle, Parikshit N. (Studies in Big Data, 2022)
XVI, 116 p. 32 illus., 28 illus. in color.